THE INFLUENCE OF SMARTPHONES ON STUDENTS' SPEAKING SKILLS - Mayu, Wandi Abi; Nappu, Syamsiarna; Saiful (Journal of Computer Interaction in Education, 2024)
The aim of this research is to find out the Effect of Smartphone on Students’ Speaking Skill. The research design was used pre-experimental research with one group pre-test and post-test. This research was conducted at SMP Negeri 2 Pattallassang sub-district of gowa. The researcher was used total sampling technique. The researcher uses this technique because all the members of the selected had similar characteristic and the same relatively baseline knowledge based on their test examination average scores. The total number of samples was 30 students from class VII-5. The Speaking tests were administered in the pretest and posttest. The instrument was intended to measure the students’ enrichment of speaking. The test Speaking aspects in this research are: fluency, vocabulary, pronunciation, accuracy and comprehensibility. Based on the research findings and discussion in the previous chapter, the researcher concludes that the use of Smartphone enriches the students’ speaking skill; it is proved by the mean score of the students’ posttest. The t-test of the students’ speaking achievement in posttest was smaller than α (0.000 < 0.05). It meant that the H1 of the hypothesis was accepted.